Diretrizes para gestão da qualidade em bibliotecas universitárias: uma análise entre Brasil e Alemanha - Lima, Juliana de Sousa (2025)
University libraries play a fundamental role in supporting teaching, research, and extension activities. However, they face ongoing challenges due to technological transformations, shifts in academic practices, and increasing user expectations. In this context, it is essential to adopt strategies that ensure efficient and up-to-date services. Quality Management emerges as an effective approach by introducing systematic methods for continuous improvement. When applied to libraries, it can optimize internal processes, standardize services, enhance user satisfaction, and improve institutional performance. Therefore, it is crucial to understand how Quality Management can be implemented and what benefits it may bring to these organizations. This study seeks to answer the following central question: What is the potential of Quality Management in the development of information products and services, based on national and international guidelines, within the context of university libraries? To address this, the research aims to propose adapted Quality Management guidelines for university libraries, focusing on the continuous improvement of the services and products offered, while considering the specific characteristics and needs of each institutional context. Methodology: The research is of an applied nature, with a qualitative character and exploratory objectives. The study examines the Library System of the Federal University of Ceará (UFC) in Brazil and university libraries in Germany, with the Central Library of the Pici Campus Prof. Francisco José de Abreu Matos (BCCP) and the University of Vechta Library serving as case studies. Data were collected through semi-structured interviews and participant observation. Analysis was based on Bardin's (2011) content analysis method, organized into thematic categories: university libraries, Quality Management, and the librarian's role in this context. The research process included a literature review, an in-depth study of the selected libraries, data collection and analysis, and the development of management guidelines. Results: The findings indicate that university libraries in Brazil and Germany share core principles of Quality Management, such as the pursuit of continuous improvement and user satisfaction. However, the implementation of these concepts varies by context. In both libraries, Quality Management appears to be integrated into the organizational culture, as seen in documented processes, ongoing performance evaluation, and greater staff autonomy in driving improvements. One of the main challenges identified is the need for increased staffing, as limited human resources often hinder the implementation of improvement initiatives. Conclusion: The study concludes that the implementation of Quality Management in university libraries is a dynamic process that can be adapted to various institutional and cultural contexts. The proposed guidelines represent a viable path toward enhancing library services in their unique realities.